2021
DOI: 10.17221/190/2020-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cultivation media and NaCl concentration on the growth kinetics and biogenic amine production of Lactobacillus reuteri

Abstract: We analysed and compared the ability of four strains of Lactobacillus reuteri of sheep origin ranked as NSLAB (non-starter lactic acid bacteria) to grow and produce biogenic amines (BA) under cultivation conditions varying in cultivation media and salt content. The production of biogenic amines was primarily dependent on the growth rate of L. reuteri under particular cultivation conditions. From among produced BA, tyramine appeared as the dominant one while L. reuteri CCM 3644 possessed the most potent aminoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…SLAB, NSLAB and other microorganisms have been reported as decarboxylase-producing bacteria [ 28 , 126 ], which has been proven for several Lactobacillus strains, for example, L. acidophilus PNW3 [ 127 , 128 , 129 , 130 ], including halotolerant Lactobacillus species [ 131 , 132 ]. Body et al [ 133 ] have reported the higher the salt concentration (up to 3%) the higher BAs production by L. reuteri strains, which is consistent with the results obtained in the present study. For other fermented foods, positive correlations between Lactobacillus and different BAs have also been reported, such as TYR, PUT or HIS [ 134 , 135 ], but results differ according to the product [ 136 ].…”
Section: Discussionsupporting
confidence: 93%
“…SLAB, NSLAB and other microorganisms have been reported as decarboxylase-producing bacteria [ 28 , 126 ], which has been proven for several Lactobacillus strains, for example, L. acidophilus PNW3 [ 127 , 128 , 129 , 130 ], including halotolerant Lactobacillus species [ 131 , 132 ]. Body et al [ 133 ] have reported the higher the salt concentration (up to 3%) the higher BAs production by L. reuteri strains, which is consistent with the results obtained in the present study. For other fermented foods, positive correlations between Lactobacillus and different BAs have also been reported, such as TYR, PUT or HIS [ 134 , 135 ], but results differ according to the product [ 136 ].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, Lactobacillus salivarius (GCI9) and W. confusa (ACI2) displayed lower NaCl tolerance. As emphasized in the studies by Vasiee et al [ 9 ] and Body et al [ 35 ] in industrial applications, LAB must demonstrate the ability to endure salt stress conditions, as variations in NaCl concentration can influence the production of metabolites with potential health implications.…”
Section: Discussionmentioning
confidence: 99%